2008
DOI: 10.1016/j.chemosphere.2007.06.086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pollutants on laccase activities of Marasmius quercophilus, a white-rot fungus isolated from a Mediterranean schlerophyllous litter

Abstract: Marasmius quercophilus is a white-rot fungus involved in carbon recycling in Mediterranean ecosystems because of its laccase production. Here we described the effect of metal ions and halide salts, on laccase activity in order to point out the action of such environmental pollutants on this enzyme of major importance. Furthermore we tested organic solvent effects on laccase reaction since reaction mixture including solvent can be used in the transformation of xenobiotics. In the case of metal ions, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
2
27
1
1
Order By: Relevance
“…Heavy metal ions which are common environmental pollutants with strong toxicity can affect the activity and stability of laccase [37]. However, this enzyme was not affected by the addition of metal ions such as Cu 2+ , Mn 2+ , Zn 2+ , Na + , K + , Mg 2+ , Ba 2+ , and Ca 2+ at 5 mM, and it was slightly promoted by Cu 2+ , Mn 2+ , Zn 2+ , and Na + .…”
Section: Discussionmentioning
confidence: 96%
“…Heavy metal ions which are common environmental pollutants with strong toxicity can affect the activity and stability of laccase [37]. However, this enzyme was not affected by the addition of metal ions such as Cu 2+ , Mn 2+ , Zn 2+ , Na + , K + , Mg 2+ , Ba 2+ , and Ca 2+ at 5 mM, and it was slightly promoted by Cu 2+ , Mn 2+ , Zn 2+ , and Na + .…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, CuSO 4 or MnSO 4 (10 mM) showed no inhibition to the enzyme activity. In comparison to the laccases from other white-rot fungi [28][29][30] including an isolate of Pycnoporus 31 , it was found that P. coccineus Thongkred 013 BCU laccase was more sensitive to SDS, EDTA, and almost all ions tested, except for Mn 2+ .…”
Section: Fungal Collection and Screening For Laccase Producermentioning
confidence: 90%
“…Laccase of Bacillus sp. HR03 lost half of its activity at 0.7 M of NaCl, while 7.5 mM of NaCl inhibited 50% of laccase activity from a white-rot fungus, Marasmius quercophilus [13]. Furthermore, the enzyme from Bacillus halodurans was stimulated rather than inhibited with increasing concentrations of NaCl (up to 100 mM) [27].…”
Section: Biochemical Characterization Of Cotamentioning
confidence: 98%